Cell cycle in sporadic melanoma - Czajkowski, Rafał; Drewa, Tomasz; Woźniak, Alina; Krzyżyńska-Malinowska, Ewa (International journal of dermatology, 2002)
Sporadic melanoma is a neoplasm whose etiology has not been fully investigated. Contemporary achievements in molecular biology have made it possible to localize the genes whose damage can contribute to the initiation of neoplastic transformation of melanocytes and lead to a progression of the disease. The majority of these genes are responsible for the correct progression of phase G1 of the cell cycle. Phase G1 of the cell cycle is subject to control by many protooncogenes and antioncogenes, which constitute the pRb or p53 pathway, damage to which can lead to the development of malignant melanoma. The present paper discusses disorders in the control of phase G1 of the cell cycle in sporadic melanoma.